The behavior of organization in economic crisis: integration, interpretation, and research development - Potocan, Vojko (Journal of business ethics, 2021)
We investigated the significance of an economic crisis for organizations’ ethical behavior, employees’ unethical behavior, and association. To capture the effect of the “2008’ World economic crisis,” we compared the behaviors of organizations and employees’ unethical behavior during a crisis with their behavior in more favorable circumstances before and after the crisis. We used structural equation modeling to analyze answers collected from 2024 employees in Slovenian organizations between 2006 and 2016. The results showed significant growth of organizational engagement in ethical behavior, despite the crisis in the middle of the observed period. The employees’ unethical behavior was significantly less acceptable in crisis compared to before the crisis, while after the crisis, its acceptability increased again, despite not significant. The aggregate sample revealed a significantly negative influence of employee’s unethical behavior on organizations’ ethical behavior that was not significantly different across the considered periods. The research suggests the need to manage the organization’s ethical behavior in times of economic downturn, like in the present COVID 19. Additionally, managers need to devote more attention to prevent employees’ unethical behavior and its influence on organizations’ ethical behavior.